Acronychiabaueri Analogue Derivative-Loaded Ultradeformable Vesicles: Physicochemical Characterization and Potential Applications - Di Francesco, Martina; Primavera, Rosita; Fiorito, Serena; Cristiano, Maria Chiara; Taddeo, Vito Alessandro; Epifano, Francesco; Di Marzio, Luisa; Genovese, Salvatore; Celia, Christian (Planta Medica, 2017)
Elastic and ultradeformable liposomes were synthesized and physicochemically characterized to make suitable topical formulations for delivering the anti-inflammatory and anticancer compound 3-(4′-geranyloxy-3′-methoxyphenyl)-2-trans-propenoic acid. The average sizes of elastic and ultradeformable liposomes are below 300 nm, while the size distribution and Z-potential are below 0.3 and − 25 mV, respectively. The presence of 3-(4′-geranyloxy-3′-methoxyphenyl)-2-trans-propenoic acid does not affect the physicochemical parameters of nanovesicles. Elastic and ultradeformable liposomes show a zero order release kinetic and are stable at room temperature for a long time with or without 3-(4′-geranyloxy-3′-methoxyphenyl)-2-trans-propenoic acid. The ultradeformable liposomes are more deformable than elastic liposomes. These differences may depend on sodium cholate derivatives making nanoformulations. The 3-(4′-geranyloxy-3′-methoxyphenyl)-2-trans-propenoic acid-loaded elastic and ultradeformable liposomes can provide innovative nanotherapeutics-based natural compounds for the potential treatment of cutanous inflammation.
Keywords: Acronychiabaueri species; elastic liposomes; ultradeformable liposomes; ethosomes; transfersomes; deformability study